Mission at Nuremberg : an American army chaplain and the trial of the Nazis - Townsend, Tim (Journalist), (William Morrow, an imprint of HarperCollins Publishers, 2014)
This is the gripping story of the American army chaplain sent to save the souls of the Nazis incarcerated at Nuremberg. Lutheran minister Henry Gerecke was fifty years old when he enlisted as an army chaplain during World War II. As two of his three sons faced danger and death on the battlefield, he tended to the battered bodies and souls of wounded and dying GIs outside London. But at the close of the European theater, with Hitler defeated and scores of American troops returning home to resume their lives, he received his most challenging assignment: he was sent to Nuremberg to minister to the twenty-one imprisoned Nazi leaders awaiting trial for crimes against humanity. This work unearths groundbreaking new research and compelling firsthand accounts to take us deep inside the Nuremberg Palace of Justice, into the very cells of the accused and the courtroom where they answered to the world for their crimes. Never before in modern history had man accomplished mass slaughter with such precision. These twenty-one Nazis had sat at the right hand of Adolf Hitler; Hermann Goering, Albert Speer, Wilhelm Keitel, Hans Frank, and Ernst Kaltenbrunner were the orchestrators, and in some cases the direct perpetrators, of the most methodical genocide in history. As the drama leading to the court's final judgments unfolds, the author brings Henry Gerecke's impossible moral quandary to life: How, having risked his own life (and those of his sons) to eliminate the Nazi threat, could he now win the confidence of these men? In the months after the war ended, Gerecke had visited Dachau. He had touched the walls of the camp's crematorium. He had seen the consequences of the choices these men had made, the orders they had given and carried out. As he worked to form compassionate relationships with them, how could he preach the gospel of mercy, knowing full well the devastating nature of the atrocities they had committed? And as the day came nearer when he had to escort these men to the gallows, what comfort could he offer and what promises of salvation could he make "to evil itself" Detailed, harrowing, and emotionally charged, this is an incisive history of the Nuremberg trials as well as a nuanced reflection on the nature of morality and sin, the price of empathy, and the limits of forgiveness.